Injuries in women and men handball players: What do coaches need to know? A comprehensive analysis over three seasons and 154 games - Andreottola, G.; Ongaro, A.; Ferreira, J.; Crognale, D. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction Handball is a fast-paced Olympic ball game characterized by both defensive and offensive actions aimed at scoring goals. Performance in handball is influenced by a multitude of factors and it involves a range of actions including throws, passes, jumps, hits, blocks and runs. Athletes may experience muscle injuries such as strains and tears due to the rapid movements and accelerations during the game. Furthermore, collisions with opponents and physical contact can lead to traumas such as bruises, contusions and joint sprains. Handball players are also at risk of upper limb injuries, particularly to the hands and wrists, due to the fastball throws and passes. The aim of this study was to monitor number and details of injuries occurring during official Handball matches to enhance current knowledge, awareness and understanding for coaches and practitioners.